(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Geographically, prevalence of HIV/AIDS in Nigerian States can be classified into high, medium and low with Adamawa State falling into the medium category (between 1% – 1.9%). Despite several measures and interventions put in place to mitigate the burden of HIV/AIDS in the state, its prevalence has fluctuated with certain age groups carrying a far greater burden than the rest of the population. This paper examines the association between some key factors and HIV/AIDs prevalence in Adamawa State, Nigeria using the Log-linear model approach. Data was collected on 3,779 patients infected with HIV/AIDs who came for treatment at Specialist Hospital, Yola, Adamawa State drawing information on their gender, age, viral load, and marital status from 2019 to 2020. Data analysis was done using the R programming software version 3.6.3. Fourteen (14) log-linear models were fitted examining mutual and conditional independence of the study factors and all possible pairwise (and three-way) associations. The results show that progression to AIDS following HIV diagnosis differed depending on the age at diagnosis, marital status, viral load and gender. Therefore, there is need to sustain efforts at reducing the prevalence of HIV in this regard.